2019
DOI: 10.1016/j.jenvman.2019.03.086
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the potential use of a dairy industry residue to induce denitrification in polluted water bodies: A flow-through experiment

Abstract: Evaluating the potential use of a dairy industry residue to induce denitrification in polluted water bodies: a flow-through experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Less enriched signatures of δ 15 N-NO 3 − and δ 18 O-NO 3 − at 10°C, emphasize the differences in denitrification for both temperatures and illustrate that less denitrification occurs with acetate at 10°C. Furthermore, ε 15 N/ε 18 O values from 1.06 to 1.92 are in agreement with published data for induced biodenitrification, where in laboratory experiments values close to 1 (Carrey et al, 2013;Margalef-Marti et al, 2019) and on the field-scale values close to 2 are obtained (Critchley et al, 2014; Otero Despite successfully initiated denitrification, results show different NO 3 − degradation efficiencies of the C compounds. At first glance, glucose seems to be the best choice for enhanced NO 3 − degradation.…”
Section: Discussionsupporting
confidence: 91%
“…Less enriched signatures of δ 15 N-NO 3 − and δ 18 O-NO 3 − at 10°C, emphasize the differences in denitrification for both temperatures and illustrate that less denitrification occurs with acetate at 10°C. Furthermore, ε 15 N/ε 18 O values from 1.06 to 1.92 are in agreement with published data for induced biodenitrification, where in laboratory experiments values close to 1 (Carrey et al, 2013;Margalef-Marti et al, 2019) and on the field-scale values close to 2 are obtained (Critchley et al, 2014; Otero Despite successfully initiated denitrification, results show different NO 3 − degradation efficiencies of the C compounds. At first glance, glucose seems to be the best choice for enhanced NO 3 − degradation.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it was decided to evaluate the feasibility of adding an external electron donor source to promote NO3attenuation when operating at a ~16 L/s flow rate. experiments and other denitrification studies (Carrey et al, 2014;Margalef-Marti et al, 2019;Vidal-Gavilan et al, 2013). The maximum NH4 + concentration of 0.02 mM was measured at H3 after 7 d, while it decreased by the outlet (H6) to 0.01 mM in both campaigns, pointing to a nonsignificant contribution of DNRA.…”
Section: Performance Of the Cw Before Application Of Stubblementioning
confidence: 70%
“…Since the use of pure reagents such as glucose, acetate, or ethanol may be expensive in long-term treatments, the use of industrial or agricultural residues that are rich in organic C could represent a more sustainable solution. Solid products such as animal or vegetal waste (Grau-Martínez et al, 2017;Si et al, 2018;Trois et al, 2010), as well as industrial liquid by-products (Carrey et al, 2018;Margalef-Marti et al, 2019), have already been reported as being useful for promoting denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental pollution is a global problem with a strong impact on the human health [1] and food security [2]. One of the major issues is the water pollution [3,4] by residual industrial liquids (RILs). Thus, a wide range of methodologies such as adsorption [5,6], biodegradation [4,7], and the so-called advanced oxidation processes (AOPs) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] have been applied for the treatment of polluted water.…”
Section: Introductionmentioning
confidence: 99%